A novel specific peroxisome proliferator‐activated receptor γ (PPARγ) modulator YR4‐42 ameliorates hyperglycaemia and dyslipidaemia and hepatic steatosis in diet‐induced obese mice. Issue 11 (5th September 2019) - Huan, Yi; Pan, Xuan; Peng, Jun; Jia, Chunming; Sun, Sujuan; Bai, Guoliang; Wang, Xing; Zhou, Tian; Li, Rongcui; Liu, Shuainan; Li, Caina; Liu, Quan; et al.
Abstract: Aims: To evaluate a novel tetrahydroisoquinoline derivative YR4‐42 as a selective peroxisome proliferator‐activated receptor γ (PPARγ) modulator (SPPARM) and explore its anti‐diabetic effects in vitro and in vivo . Materials and methods: Using two standard full PPARγ agonists rosiglitazone and pioglitazone as controls, the PPARγ binding affinity and transactivation action of YR4‐42 were evaluated using biochemical and cell‐based reporter gene assays. The capacity of YR4‐42 to recruit coactivators of PPARγ was also assessed. The effects of YR4‐42 on adipogenesis and glucose consumption and PPARγ Ser273 phosphorylation were investigated in 3T3‐L1 adipocytes. The effects of YR4‐42 and pioglitazone, serving as positive control, on glucose and lipids metabolism were investigated in high‐fat diet‐induced obese (DIO) C57BL/6J mice. The expression of PPARγ target genes involved in glucose and lipid metabolism was also assessed in vitro and in vivo . Results: In vitro biochemical and cell‐based functional assays showed that YR4‐42 has much weaker binding affinity, transactivation, and recruitment to PPARγ of the coactivators thyroid hormone receptor‐associated protein complex 220 kDa component (TRAP220) and PPARγ coactivator 1‐α (PGC1α) compared to full agonists. In 3 T3‐L1 adipocytes, YR4‐42 significantly improved glucose consumption without a lipogenesis effect, while blocking tumour necrosis factor α‐mediated phosphorylation of PPARγ at Ser273, thereby upregulating the expression of the PPARγ Ser273 phosphorylation‐dependent genes. Furthermore, in DIO mice, oral administration of YR4‐42 ameliorated the hyperglycaemia, with a similar insulin sensitization effect to that of pioglitazone. Importantly, YR4‐42 also improved hyperlipidaemia‐associated hepatic steatosis without weight gain, which avoids a major side effect of pioglitazone. Thus, YR4‐42 appeared to selectively modulate PPARγ responses. This finding was supported by the gene expression analysis, which showed that YR4‐42 selectively targets PPARγ‐regulated genes mapped to glucose and lipid metabolism in DIO mice. Conclusions: We conclude that YR4‐42 is a novel anti‐diabetic drug candidate with significant advantages compared to standard PPARγ agonists. YR4‐42 should be further investigated in preclinical and clinical studies.